Something from Nothing: Estimating Consumption Rates Using Propensity Scores, with Application to Emissions Reduction Policies - Nicholas Bardsley; Milena Büchs; Sylke V. Schnepf (Institute for the Study of Labor (IZA), 2016)
Consumption surveys often record zero purchases of a good because of a short observation window. Only mean consumption rates can then be inferred. We show that propensity scores can be used to estimate each unit's consumption rate, revealing the distribution. We demonstrate the method using the UK National Travel Survey, in which c.40% of motorist households purchase no fuel. Estimated consumption rates are plausible judging by households' annual mileages, and highly skewed. We apply the same approach to estimate CO2 emissions and direct outcomes of a carbon cap or tax. Analysis of such policies based solely on means appears to have a negative bias, because of skewness of the underlying distributions. The regressiveness of a simple tax or cap is overstated, and redistributive features of a revenue-neutral policy are understated.
Keywords: C13; D04; D12; H23; 330; emissions reduction; fuel consumption; infrequent purchase; propensity score matching; surveys